2009
DOI: 10.1007/s12206-008-1127-9
|View full text |Cite
|
Sign up to set email alerts
|

Upper bound analysis of extrusion from square billets through circular and square/rectangular dies

Abstract: Upper bound elemental technique (UBET) for prediction of extrusion pressure in three-dimensional forward extrusion process is presented. Using square/rectangular billets, the study of the effect of die land length has been extended for the evaluations of extrusion pressures to extrude sections such as circular, square and rectangular shaped sections with power of deformation due to ironing effect at the die land taken into account. The extrusion pressure contributions due to the die land evaluated theoreticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Upper Bound Theorem (UBT), as a solution not only provides the minimum load value which ensures its deformation, but allows to discriminate the parameters that is possible to introduce in the equations optimizing process conditions [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Upper Bound Theorem (UBT), as a solution not only provides the minimum load value which ensures its deformation, but allows to discriminate the parameters that is possible to introduce in the equations optimizing process conditions [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although FE modeling provides a rather accurate and visual description of material flow, stress and strain distribution during the process, it requires a relatively considerable amount of computing time; in some complicated cases a few days to get an accurate result for just one specific case [141]. More importantly, FE modeling is unable to provide a so-called comprehensive solution, and it needs to be conducted for each specific condition on a case by case basis.…”
Section: Analytical Modeling Of Microforming Processesmentioning
confidence: 99%
“…The material-die contact after this length has no or limited effect on the energy loss. In this work, based on [141], the normalized effective die land length is assumed as 1 The other important factor to be considered was friction. Becker et al [20] reported that using the coulomb friction model sometimes can lead to a better solution in metal forming modeling [72].…”
Section: Extrusion (Zone Ii)mentioning
confidence: 99%